STUDI KASUS: PENANGANAN PUTING LECET PADA IBU MENYUSUI - Siska Febrina Fauziah; Rahmawati Musiin (Jurnal Kebidanan, 2022)
Exclusive breastfeeding is recognized as the single most effective preventive intervention to reduce child mortality in the world. Unfortunately, the success of this exclusive breastfeeding has still a lot of obstacles in daily practice. Breast pain due to nipple crack is one of the most common reasons for premature weaning of breastfeeding. This case study describes the management of midwifery care for Mrs. A, a 29-years-old primipara, who experienced nipple crack on the 19th day of postpartum. She was confused because her baby refused to be given milk formula while she had difficulty giving breastmilk because her nipple soreness. Expressed Breastmilk (EBM) was suggested to be applied topically on the nipple to heal the crack. Meanwhile correction of position and attachment as well as breast care were suggested to prevent repeated nipple trauma. The midwifery care provided in this case made Mrs. A was able to breastfeed her baby comfortably and the sores on her nipple had completely healed within 8 days. Single intervention is not enough to treat nipple crack for breastfeeding mothers. It is necessary to provide combination of continuous midwifery interventions so that the results are more effective. Interventions to prevent nipple trauma in breastfeeding mothers which include correct breastfeeding positions and techniques, breast care and EBM for topical use should be given as standard information provided by health workers in antenatal and postnatal counseling to ensure continuity of breastfeeding and the success of exclusive breastfeeding.